Fatores que afetam a qualidade de vida no trabalho: uma análise em um Instituto Federal de Ensino - Silva, Ana Carolina Cozza Josende da (2015)
The Quality of Working Life has received much importance in the current scenario, where work has become very important in people s lives and can positively or negatively affect the quality of life of individuals. For a long time when discussing quality in companies, the production was mainly emphasized. Today, not only quality at work is discussed but also quality of employees lives, linked directly with employee satisfaction by making the creation of an environment in which everyone feels good required. Within this context, this study aimed to analyze and to identify factors associated with the Quality of Life at Work of the servers of the Instituto Federal Farroupilha - at Campus Alegrete . To do so, an exploratory literature was developed about the objectives, quantitative as to the nature, being carried out through a case study. Data were obtained with the aid of two questionnaires: one on the Profile and Data Professional of the servers and the other called QWLQ-78, designed to measure the Quality of Life at Work. Initially, there was a descriptive analysis of the profile and professional data servers. A multivariate analysis was subsequently performed, using cluster analysis and factor analysis (principal component extraction method) in order to identify factors that could affect the Quality of Life at Work. The results of the analysis showed that 57% of respondents were female, with a mean of 35 years old, predominantly single workers (46,8%), without children (54,1%), with insurance (82,8 %), with an average time of 2 years and 11 months institution, and 53,5% teachers. Considering the analysis of the Quality of Life instrument there was an overall average score of 3,57. In the cluster analysis was possible to make a reduction from 78 to 52 variables. Using factor analysis, we selected 14 factors, which explain 64,9% of the variation, and is considered a satisfactory value. Considering these factors, eight were assessed as satisfactory by the servers, four were assessed as neutral, one as unsatisfactory and one as very unsatisfactory. Thus, it is concluded that, in general, the employees of this institution reported quality of life in satisfactory work, but that can be improved in some aspects, such as reducing fatigue and the practice of professional activities, which may contribute to the improvement the satisfaction of servers.